2015
DOI: 10.1371/journal.pone.0119313
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Risk of Bladder Cancer: A Dose-Response Meta-Analysis of 15 Cohort Studies

Abstract: BackgroundEpidemiological studies have reported inconsistent association between obesity and risk of bladder cancer, and the dose-response relationship between them has not been clearly defined.MethodsWe carried out a meta-analysis to summarize available evidence from epidemiological studies on this point. Relevant articles were identified by searching the PubMed and Web of Science databases through September 30, 2014. We pooled the relative risks from individual studies using random-effect model, and the dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 48 publications
2
79
0
Order By: Relevance
“…A recent meta-analysis from 16 cohort studies suggested a linear relationship between BMI and risk of urothelial cancer [20]. However, the relation between BMI and the percentage of body fat depends on age and sex, and differs across ethnic groups [8].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis from 16 cohort studies suggested a linear relationship between BMI and risk of urothelial cancer [20]. However, the relation between BMI and the percentage of body fat depends on age and sex, and differs across ethnic groups [8].…”
Section: Discussionmentioning
confidence: 99%
“…In the Sun et al (11) meta-analysis, the extracted point estimates relative to normal weight from Song et al (12) for BMI categories 25.0 to 27.4; 27.5 to 29.9; 30.0 to 34.9; and greater than or equal to 35.0 kg/m 2 for men were: 1.48; 1.95; 1.47, 1.91 and for women were: 2.59, 2.69; 2.63, 1.93. Yet, the continuous BMI plots in Figure 1 of Song et al (12) indicate that the BMI-risk relation was absolutely null with risk near 1.00 across the full BMI range.…”
Section: Tablementioning
confidence: 99%
“…Thus, during evaluation, the IARC working group referred to the WCRF bladder cancer report based on 22 prospective cohort studies, which reported no significant association with between obesity and bladder cancer incidence (9). But two additional meta-analyses of prospective cohort studies (10, 11), searching very similar timeframes, identified substantially different study numbers. These analyses reported significant positive associations and (and in contrast to the WCRF analysis) concluded that BMI was associated with an increased risk of bladder cancer (Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations